1994
DOI: 10.1111/j.1439-0434.1994.tb00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhizoctonia solani associated with Sore Shin and Leaf Spot Symptoms on Tobacco in Zimbabwe

Abstract: The relationship between Rhizoctonia solani isolates derived from leaf spot and sore shin symptoms on tobacco was characterized by determining nuclear number, hyphal diameter, anastomosis grouping (AG) and pathogenicity. The leaf spot isolates had significantly more nuclei per cell, and wider hyphae than the sore shin isolates. Anastomosis pairings with known tester strains confirmed the leaf spot isolates to be AG 3, and the sore shin isolates to be AG 4. Pathogenicity testing indicated that the leaf spot iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This is a detail investigation to provide evidence of the relative AG composition of R. solani populations causing disease in China tobacco. So far isolates belonging to AGs 1 through 5 of R. solani have been reported as causal agents of tobacco diseases [12,15]. Anastomosis pairing revealed that all isolates were belonging to AG-3.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is a detail investigation to provide evidence of the relative AG composition of R. solani populations causing disease in China tobacco. So far isolates belonging to AGs 1 through 5 of R. solani have been reported as causal agents of tobacco diseases [12,15]. Anastomosis pairing revealed that all isolates were belonging to AG-3.…”
Section: Discussionmentioning
confidence: 95%
“…Pathogencity tests were performed on detached tobacco (cv. nc89) leaves; 4-week-old seedlings were planted in a greenhouse (25-35°C day/15-20°C night temperatures) with no additional lighting according to Mopfu and Julian [12]. YC-9 isolates was retrieved from slant tube preservation and grown on PDA at 28℃ in the dark for 5 days.…”
Section: Diseased Samples Examination Of and Pathogen Isolationmentioning
confidence: 99%